FOXC2 Autoregulates Its Expression in the Pulmonary Endothelium After Endotoxin Stimulation in a Histone Acetylation-Dependent Manner - Xia, Sheng; Yu, Wei; Menden, Heather; Younger, Scott T.; Sampath, Venkatesh (Frontiers in Cell and Developmental Biology, 2021)
The innate immune response of pulmonary endothelial cells (EC) to lipopolysaccharide (LPS) induces Forkhead box protein C2 (FOXC2) activation through Toll Like Receptor 4 (TLR4). The mechanisms by which FOXC2 expression is regulated in lung EC under LPS stimulation remain unclear. We postulated that FOXC2 regulates its own expression in sepsis, and its transcriptional autoregulation directs lymphatic EC cell-fate decision. Bioinformatic analysis identified potential FOXC2 binding sites in the FOXC2 promoter. In human lung EC, we verified using chromatin immunoprecipitation (ChIP) and luciferase assays that FOXC2 bound to its own promoter and stimulated its expression after LPS stimulation. Chemical inhibition of histone acetylation by garcinol repressed LPS-induced histone acetylation in the FOXC2 promoter region, and disrupted LPS-mediated FOXC2 binding and transcriptional activation. CRISPR/dCas9/gRNA directed against FOXC2-binding-element (FBE) suppressed LPS-stimulated FOXC2 binding and autoregulation by blocking FBEs in the FOXC2 promoter, and repressed expression of lymphatic EC markers. In a neonatal mouse model of sterile sepsis, LPS-induced FOXC2 binding to FBE and FOXC2 expression in lung EC was attenuated with garcinol treatment. These data reveal a new mechanism of LPS-induced histone acetylation-dependent FOXC2 autoregulation.